COLOSTOMY IN COMPLICATIONS OF SURGICAL CORRECTION ANORECTAL MALFORMATION IN CHILDREN - BOZOROV SHAVKAT TOJIDDINOVICH,ADHAM ANVAROVICH GAFUROV,TURAKULOV ZOIRJON SHOKIROVICH (Ethiopian International Journal of Multidisciplinary Research, 2024)
Anorectal malformations in children are still one of the most difficult problems in pediatric coloproctology. Most pediatric surgeons continue to adhere to the opinion that preliminary colostomy and delayed proctoplasty are expedient, motivating this tactic by the possibility of creating the optimal conditions for performing a complex intervention, reducing the anesthetic risk, and avoiding technical errors. The work is based on the results of treatment of 154 children with anorectal malformation, with a preliminary colostomy. The use of colostomy in children with anorectal malformation made it possible to carry out the necessary surgical tactics in a timely and differentiated manner, reduce the frequency and nature of complications and early disability, improve the quality of life and social adaptation of patients.